Chicken soup for the soul a book of miracles ; 101 true stories of healing, faith, divine intervention, and answered prayers - Canfield, Jack 1944-; Hansen, Mark Victor; Thieman, LeAnn (Chicken Soup for the Soul Publishing, 2010)
A collection of 101 true personal stories in which the contributors recount miracles that have happened to them and attribute the miracles to God, Jesus, or other Christian entities to whom they prayed. Stories are about instances of miraculous healing, answered prayers, divine intervention, faith, and divine appointments.